2024
DOI: 10.3389/fsufs.2023.1282427
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the nutritional and functional values of common bean by farming system: organic vs. conventional

Roberto Rodríguez Madrera,
Ana Campa Negrillo,
Juan José Ferreira Fernández

Abstract: Common bean (Phaseolus vulgaris L.) is a crop of high nutritional interest which is widespread throughout the world as a result of which it is considered as a potential crop for ensuring future food security. The effect of organic and conventional farming systems on the nutritional and functional composition of two cultivars of market class fabada (a landrace and a modern elite cultivar) is described. The findings of our study have shown that the common beans from organic farming have a higher content of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(84 reference statements)
1
1
0
Order By: Relevance
“…As a consequence of these differences, the Mesoamerican gene pool had the highest levels of TFA, SFA and UFA, and the Andean and middle gene pools had the lowest ω-6/ω-3 ratio. In addition, significant differences (p < 0.05) were detected between years of cultivation for stearic, oleic and linolenic acids (Table 3), which shows the influence of environmental conditions on the FA profile, in agreement with previous reports [28,55].…”
Section: Gene Pool and Fatty Acid Content In Dry Beansupporting
confidence: 91%
See 1 more Smart Citation
“…As a consequence of these differences, the Mesoamerican gene pool had the highest levels of TFA, SFA and UFA, and the Andean and middle gene pools had the lowest ω-6/ω-3 ratio. In addition, significant differences (p < 0.05) were detected between years of cultivation for stearic, oleic and linolenic acids (Table 3), which shows the influence of environmental conditions on the FA profile, in agreement with previous reports [28,55].…”
Section: Gene Pool and Fatty Acid Content In Dry Beansupporting
confidence: 91%
“…Various studies have reported interesting information about the FA in dry beans, pointing out the variability within the species and the influence of growing conditions on its profile [16,18,[24][25][26][27][28]. These reports show the FA profiles expressed as a percentage of fatty acid in the total fat previously extracted.…”
Section: Introductionmentioning
confidence: 99%